Cobalt-based catalyst, preparation method thereof and application of cobalt-based catalyst in electrolytic hydrogen production
The cobalt-based catalyst generated on the electrode by electrochemical deposition method solves the problems of high cost of existing precious metal-based catalysts and complex preparation process, and realizes the oxygen evolution function of efficiently decomposing water in neutral water and seawater, and has good results. The reproducibility and stability of the product are suitable for industrial applications of electrolytic hydrogen production.
Patent Information
- Application Number
- CN202411581269.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing electrolytic hydrogen production technology, the high cost and scarcity of precious metal-based catalysts limit their application, and the preparation process of cobalt-based catalysts is complex and has poor reproducibility.
The electrochemical deposition in situ generation method is used to generate a cobalt-based catalyst on the electrode, which consists of nanocobalt oxide and nanocobalt hydroxide. The preparation method is simple, intuitive and easy to control, and does not require additional binder.
This cobalt-based catalyst has obvious oxygen evolution function in neutral water and seawater, can effectively decompose water molecules, and the preparation method has good reproducibility and stability, which is suitable for industrial applications.
Smart Images

Figure CN119465225A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytic hydrogen production, and in particular to a cobalt-based catalyst and a preparation method thereof and application thereof in electrolytic hydrogen production. Background Art
[0002] Water electrolysis, especially when combined with renewable energy sources (i.e., photovoltaics, hydropower, and wind power, among others), has long been proposed as a sustainable energy solution in the hydrogen economy to address intermittent electricity challenges and alleviate dependence on fossil fuel technologies for energy storage and utilization. Extensive R&D efforts have been devoted to improving the catalytic efficiency and optimizing the operating conditions of the two representative half reactions, hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), for integrated water splitting processes in scale-up applications. Among the major challenges in water electrolysis, the sluggish four-electron oxygen evolution half reaction and the adoption of noble metal-based catalysts are considered to be significant barriers to water splitting efficiency and its economic viability for scale-up hydrogen production.
[0003] The catalysts used in hydrogen production by water electrolysis are mainly metal oxides such as platinum group metals and IrOx. Although such metal oxides greatly accelerate the water electrolysis process, their application is limited due to their high cost and scarcity. Therefore, catalyst materials that are more in line with the needs of industrial applications, such as low cost, high abundance, and high catalytic activity, are currently one of the important research directions in the field of hydrogen production by electrolysis. To this end, CN 117187870A discloses a method for preparing a low-iridium catalyst for water electrolysis hydrogen production, comprising the steps of: S1. reacting chloroiridic acid, non-precious metal M (one or more of Cu, Fe, Mn, Co, Ni) with OH- to form an ion chelate product; S2. mixing and reacting the ion chelate product with nitrate to obtain a catalyst precursor powder; S3. calcining the catalyst precursor powder to obtain an IrMOx catalyst primary product; S4. dealloying the primary product to obtain a porous IrMOx catalyst with a core-shell structure, wherein the shell structure of the porous IrMOx catalyst is a porous Ir-rich oxidation state shell that does not contain non-precious metal M, and the core structure is an IrM alloy oxide particle. Although the porous IrMOx catalyst prepared by the method disclosed in the above patent application effectively controls the production cost, it still requires a large amount of Ir compounds and has problems such as a complicated preparation process.
[0004] Since cobalt-based catalysts are closer to the water decomposition activity of precious metals and have a much higher natural abundance and economy than precious metals, they are considered to be competitive and promising products to replace existing water electrolysis hydrogen production catalysts. Various forms and compositions of cobalt-based compounds (including cobalt nitride, phosphate, oxide) have been widely studied for water electrolysis to explore the reaction mechanism and improve the catalytic performance to achieve viable commercial applications. The catalyst layer on the existing electrode is usually synthesized by first synthesizing a cobalt-based heterogeneous catalyst and then performing electrode coating treatment; however, this method usually requires the addition of an adhesive to fix the catalyst layer, and also requires fine control of the catalyst preparation process and fine-tuning of the catalytic system to achieve the desired purpose; in addition, this method also has problems such as poor reproducibility of the catalyst layer and difficulty in controlling the preparation process. Summary of the invention
[0005] Based on this, the main purpose of the present invention is to provide a cobalt-based catalyst, a preparation method thereof and an application in electrolytic hydrogen production. The cobalt-based catalyst is generated on an electrode by an in-situ electrochemical deposition method, and has an obvious oxygen evolution function in neutral water and seawater, and is easy to decompose water molecules. In addition, the cobalt-based catalyst is formed in situ by an electrochemical deposition method, so that its preparation method is convenient, intuitive, easy to control, reproducible, and does not require additional adhesive fixation.
[0006] Specifically, the first aspect of the present invention provides a cobalt-based catalyst, which is mainly composed of nano-cobalt oxide and nano-cobalt hydroxide. Preferably, the cobalt in the cobalt-based catalyst has different oxidation states.
[0007] The second aspect of the present invention provides a method for preparing the above-mentioned cobalt-based catalyst, comprising electrolyzing KCo(III)EDTA by electrochemical deposition, wherein the structural formula of KCo(III)EDTA is
[0008]
[0009] Furthermore, the preparation method comprises the steps of: first dissolving KCo(III)EDTA in an alkaline solution to form a cobalt-containing alkaline solution; and then performing electrochemical deposition to deposit a cobalt-based catalyst in situ on the electrode surface. In the electrochemical deposition process, the electrode is preferably used as an anode to electrolyze the cobalt-containing alkaline solution.
[0010] The alkaline solution can be an alkaline solution such as potassium hydroxide, sodium hydroxide, etc. If the concentration of the alkaline solution is too low, it will lead to a lower deposition rate or even no deposition can be observed; if it is too high, it will have a faster deposition rate, making the surface structure of the prepared cobalt-based catalyst material appear more disordered under an electron microscope; therefore, its concentration can be 1 to 4M.
[0011] In the alkaline solution, if the dosage of KCo(III)EDTA is too low, less cobalt-based catalyst is generated and it is difficult to effectively play a catalytic role; if it is too high, it is easy to cause catalyst waste; therefore, its dosage is preferably 0.5-3 g / L, more preferably 1-2 g / L.
[0012] The electrochemical deposition step includes: using a three-electrode system, inserting a working electrode into the cobalt-containing alkali solution for electrochemical deposition, and in-situ deposition on the working electrode to form a cobalt-based catalyst. The cobalt-containing alkali solution can be electrolyzed and induced to be in-situ electrochemically deposited on the working electrode by an electrochemical method of cyclic voltammetry (CV), chronopotentiometry (CP) or chronoamperometry (CA). The electrochemical deposition time is preferably 0.5 to 15 hours.
[0013] The three-electrode system is a prior art, including a working electrode, a counter electrode and a reference electrode. In the electrochemical deposition process, the working electrode is used as an anode and the counter electrode is used as a cathode to electrolyze KCo(III)EDTA, so that KCo(III)EDTA is electrocatalytically decomposed, and a cobalt-based catalyst is deposited and grown on the working electrode and the counter electrode, respectively. The working electrode can be a carbon paper electrode, a glassy carbon electrode, a graphite electrode, an indium tin oxide electrode (ITO) or a reduced graphene electrode (RGO), etc.
[0014] KCo(III)EDTA is prepared by firstly reacting CoCl2 with deprotonated EDTA ligand to form a divalent cobalt complex, and then oxidizing the Co center in the divalent cobalt complex with excess hydrogen peroxide. The divalent cobalt complex is Co(II)EDTA.
[0015] In the present invention, "trivalent cobalt" and "Co(III)" both refer to trivalent cobalt atoms, and "divalent cobalt" and "Co(II)" both refer to divalent cobalt atoms. The concentration unit "M" in the present invention refers to "mol / L".
[0016] The preparation method of KCo(III)EDTA comprises: firstly keeping cobalt dichloride and EDTA at a constant temperature of 70 to 90°C for 15 to 30 minutes under stirring to form a pink suspension; then adding potassium acetate to the suspension under the constant temperature to transform the pink suspension into a magenta mixture; then adding excess hydrogen peroxide to the magenta mixture under the constant temperature, continuing to stir and react until the magenta mixture turns into a darker purple-red mixture; and hot filtering the purple-red mixture to obtain KCo(III)EDTA.
[0017] When the reaction system solution turns magenta, the trivalent cobalt product has been generated and is in a completely dissolved state at this time. Continue stirring and heating, and the reaction system solution will precipitate the trivalent cobalt product to form a purple-red mixture. Filter the mixture while hot to obtain a large amount of product KCo(III)EDTA. The filtrate after filtration still contains the trivalent cobalt product, but since the product has precipitated in large quantities, the concentration can no longer meet the supersaturation and precipitate. Therefore, more product KCo(III)EDTA is continued to precipitate and separate by concentration and ethanol recrystallization to improve the yield. Therefore, the above-mentioned preparation method of KCo(III)EDTA also includes concentrating the filtrate obtained in the above-mentioned hot filtration step and recrystallizing it with ethanol to obtain KCo(III)EDTA again.
[0018] Experiments have shown that the above cobalt-based catalyst, as a catalyst for hydrogen production by electrolysis, has an obvious oxygen evolution function in neutral water or seawater. Therefore, the third aspect of the present invention provides an application of the above cobalt-based catalyst in hydrogen production by electrolysis.
[0019] The cobalt-based catalyst provided by the present invention uses KCo(III)EDTA as a precursor and is prepared by an electrochemical deposition in-situ generation method. Since the deposited cobalt-based catalyst is mainly composed of a large number of groups containing oxygen and hydroxide, there are a large number of ionized hydroxides in the alkaline solution. Hydroxide plays an important role in supporting the stability of cobalt compounds, so it has an obvious oxygen evolution reaction in neutral water or seawater, and can be used as an anode catalyst for electrolysis of neutral water or seawater to produce hydrogen, and an oxygen evolution reaction occurs.
[0020] The preparation method of the above-mentioned cobalt-based catalyst provided by the present invention uses KCo(III)EDTA alkaline solution as a precursor and adopts an electrochemical deposition method to generate a cobalt-based catalyst in situ on an electrode. The preparation method is simple and convenient, easy to control, and has good reproducibility. It does not require an additional binder for fixing, and can form a strong binding force with the electrode. It has good stability and is not easy to fall off, which is conducive to industrial application as a catalyst for hydrogen production by electrolysis of water. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 For KCo(III)EDTA 1 H NMR spectrum;
[0022] Figure 2 For KCo(III)EDTA 13 C NMR carbon spectrum;
[0023] Figure 3 The characteristic chronopotentiogram of the anodic electrochemically deposited cobalt-based catalyst provided in Example 1 on a blank carbon paper electrode, wherein the current is 6 mA and maintained for 30 min;
[0024] Figure 4 SEM micrographs of cobalt-based catalysts deposited on the anode (left) and cathode (right) of carbon paper provided in Example 1;
[0025] Figure 5 XPS spectra of the cobalt-based catalyst deposited on the anode (left) and cathode (right) of the carbon paper provided in Example 1;
[0026] Figure 6 Characteristic polarization curves of the anode electrochemically deposited cobalt-based catalyst and the cathode electrochemically deposited cobalt-based catalyst in the oxygen evolution reaction provided in Example 1, wherein the reference electrode Hg / HgO is carried out in an O2-purged 1M KOH solution. Left: Cyclic voltammograms of the anode electrochemically deposited cobalt-based catalyst (black) and the cathode electrochemically deposited cobalt-based catalyst (red), anodic scan. Right: 14h chronopotentiograph of the anode electrochemically deposited cobalt-based catalyst (black) and the cathode electrochemically deposited cobalt-based catalyst (red), the current is 6mA;
[0027] Figure 7 A SEM micrograph of the anodic electrochemically deposited cobalt-based catalyst prepared using 4M alkali solution provided in Example 3;
[0028] Figure 8 The electrochemical performance comparison diagram of the anode electrochemically deposited cobalt-based catalyst prepared using 1M and 4M alkali solutions provided in Example 3, wherein the reference electrode Hg / HgO was O2-purged in 1M and 4M KOH solutions, 1cm 2 Blank carbon paper is used as the working electrode and the counter electrode; left: linear scan voltammogram obtained at a scan rate of 10 mV / s; right: stacked cyclic voltammogram collected at a scan rate of 50 mV / s to highlight the capacitive current signal. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0030] The terms used in the present invention are all commonly used terms in the relevant field. Unless otherwise specified, the raw materials, equipment, preparation processes, testing methods, etc. used are all prior arts in the relevant field.
[0031] In the following examples, electrochemical experiments were performed on a Wave Driver Potentiostat XX (Pine Research Instrumentation); unless otherwise stated, 1 H and 13CNMR spectra were recorded on BrukerAvance 300 MHz and Bruker Avance 500 MHz instruments, respectively; scanning electron microscopy (SEM) micrographs were recorded on a ZEISS Supra 40VP FE-SEM microscope;
[0032] Carbon paper (Freudenberg H23, Fuel Cell Store, College Station TX) was cut and calcined at 700 °C under Ar for 2 h before use;
[0033] In the three-electrode system, the reference electrode is a saturated mercury electrode Hg / HgO;
[0034] Simulated seawater (simulated sodium chloride concentration in seawater): distilled water was used to prepare a 3.5% NaCl solution.
[0035] Example 1 Cobalt-based catalyst and preparation method thereof
[0036] The embodiment of the present invention provides a cobalt-based catalyst, wherein cobalt oxide is prepared by electrochemical deposition using KCo(III)EDTA as a precursor. The specific preparation method comprises the following steps:
[0037] (1) Preparation of KCo(III)EDTA:
[0038] 1.19 g CoCl2·6H2O (5.00 mmol, 1 eq) was weighed and added to a glass bottle equipped with a stirring bar. 1.46 g EDTA (5.00 mmol, 1 eq) was weighed and mixed with CoCl2·6H2O in a vial. 6 mL of deionized water (DI H2O) was added to the vial containing the solid mixture and placed in an oil bath for stirring and heated at 85°C for about 20 min. 5 mL of CH3COOK aqueous solution (30.0 mmol, 6 eq) was slowly added to the heated water mixture. The suspension gradually became uniform and turned magenta. The reactants were stirred for another 20 min, followed by the addition of 5 mL of 6% aqueous H2O2 solution (10.0 mmol, 2 eq). The mixture was stirred for another 20 min, and the magenta color became darker, accompanied by bubbles produced by the decomposition of excess H2O2. The reaction mixture was filtered while hot, and the product was then concentrated, with the solvent volume reduced to about 5 mL. About 30 mL of ethanol was added to the concentrated mother liquor to immediately induce precipitation of the product. The dark magenta solid was collected by filtration and washed twice with ethanol (5 mL each wash).The crystalline product KCo(III)EDTA was obtained by layering the aqueous mother liquor with ethanol at room temperature to slowly diffuse the solvent.
[0039] The product KCo(III)EDTA was 1 H and13 C NMR spectroscopy analysis, the structure is shown in Figure 1 and Figure 2 As shown. Figure 1-2 In the above, we can determine that: 1) the recrystallized product has a high purity under the nuclear magnetic signal, 2) there are two sets of hydrogen signals with different chemical shifts to confirm the successful chelation of EDTA, 3) the cobalt center has a d6 outer electron configuration and shows a diamagnetic signal in a low-spin mode, which supports the strong field coordination structure characterization such as octahedral saturated coordination, so the structural formula of the crystallized product is comprehensively judged to be This demonstrates the successful synthesis of KCo(III)EDTA.
[0040] (2) Electrochemical deposition of cobalt-based catalyst: 0.16 g of KCo(III)EDTA was dissolved in 1 M KOH alkaline solution to obtain 80 mL of 5.9 mM light purple cobalt-containing alkaline solution as an electrolyte. The electrolyte was added to a typical three-electrode system. The working electrode and the counter electrode were both based on graphite rods. Alligator clips were used to clamp carbon paper directly on the graphite rods. The alligator clips were wrapped with copper strips to reduce contact resistance. The working electrode and the counter electrode were separated by about 1 cm. 2 The area of the anode is immersed in the cobalt-containing alkali solution, and the cobalt-containing alkali solution is electrolyzed by chronopotentiometry to induce an electrochemical deposition process. The characteristic anode chronopotentiograph is as follows Figure 3 As shown, the current was maintained at 6 mA for 30 min. The continuous decrease in potential during the conduction period provided an indication of the material deposition process. Under this condition, electrochemical deposition of the working electrode (anode) and the counter electrode (cathode) was observed to proceed simultaneously, and the following were obtained respectively: Figure 4 and Figure 5 The anodic electrodeposition catalyst and the cathodic electrodeposition catalyst are shown.
[0041] from Figure 4 The SEM images shown show that there are significant differences in morphology between the anodic and cathodic electrodeposition catalysts. The anodic electrodeposition catalysts are mostly amorphous, with particle sizes usually in the nanometer range, distributed on the surface of the working electrode (anode) and forming irregular film patterns. On the other hand, the cathodic electrodeposition catalysts exhibit more obvious anisotropy, with flaky particles anchored on the surface of the counter electrode (cathode); compared with the particles of the anodic electrodeposition catalysts, the flaky particles of the cathodic electrodeposition catalysts appear to be more crystalline, with larger particles, and their sizes are mostly in the micrometer range.
[0042] from Figure 5 The XPS graph shown in the figure shows that the working electrode and the counter electrode materials have different proportions of cobalt and oxygen atoms and different valence state distributions. Obviously, the anode electrodeposition catalyst and the cathode electrodeposition catalyst are two different materials. Figure 4 The conclusions are consistent.
[0043] Comparative Example 1: Electrochemical deposition was performed using free EDTA of equal molar concentration instead of KCo(III)EDTA in "(2) Electrochemical deposition of cobalt-based catalyst". Since EDTA does not contain metal, electrolysis of a 1M KOH solution containing free EDTA ligands of equal molar concentration showed substantially no water decomposition electrical signal in the same potential range.
[0044] Comparative Example 2: CoCl2 of the same molar concentration was used to replace KCo(III)EDTA in "(2) Electrochemical Deposition of Cobalt-based Catalyst" for electrochemical deposition. However, after adding CoCl2 to the 1M KOH solution, an insoluble cobalt hydroxide substance was formed, which quickly agglomerated and formed a precipitate at the bottom of the reaction container instead of being deposited on the electrode surface to initiate the electrochemical redox process.
[0045] Therefore, in combination with Comparative Examples 1-2, the presence of the cobalt-containing EDTA coordination compound KCo(III)EDTA in this embodiment is a prerequisite for the electrochemical deposition process.
[0046] Example 2 Application of cobalt-based catalyst in hydrogen production by electrolysis
[0047] The graphite rod containing the anode electrodeposition catalyst and the cathode electrodeposition catalyst provided in Example 1 was used as the working electrode, the graphite rod was used as the counter electrode, the saturated Hg / HgO electrode was used as the reference electrode, and a 1M KOH electrolyte (without KCo(III)EDTA) was prepared with simulated seawater. At room temperature, the catalyst was tested for oxygen evolution reaction (OER) performance using a three-electrode system. The results are as follows: Figure 6 shown.
[0048] Figure 6 The cyclic voltammogram shown (left) shows that the anodic electrodeposition catalyst exhibits a significantly increased capacitance signal compared to the cathodic electrodeposition catalyst. When continuing to scan to high potentials in an anodic manner, both materials exhibit an increase in the Faradaic current signal and increased effervescence on the electrode surface, while the anodic electrodeposition catalyst shows a significantly lower overpotential compared to the cathodic electrodeposition catalyst that performs an oxidative Faradaic process. Figure 6 The chronopotentiograph shown (right) indicates that both electrodeposited catalyst materials exhibit good stability under alkaline conditions. During the 14 h of the CP experiment at 6 mA, the potentials of the anode and cathode electrodeposited catalysts increased by 4 mV and 12 mV, respectively, indicating that the two electrodeposited catalyst materials have good stability under this working condition and there is no desorption.
[0049] Example 3 Cobalt-based catalyst and preparation method thereof
[0050] This embodiment provides a cobalt-based catalyst, whose structure and preparation method are basically the same as those of the cobalt-based catalyst and its preparation method provided in Example 1, with the main difference being that: the concentration of the KOH solution used in this embodiment is 4M, that is, a cobalt-containing alkaline solution formed by dissolving KCo(III)EDTA in a 4M KOH alkaline solution is used as an electrolyte to deposit an anodic electrodeposition catalyst on the working electrode, such as Figure 7 shown.
[0051] The OER performance test method provided in Example 2 was used to perform electrochemical tests on the anode electrodeposition catalysts provided in this example and Example 1. The results are as follows: Figure 8 shown. Figure 8 It shows that when other conditions remain unchanged, the concentration of the alkaline solution increases, the current signal is relatively enhanced, and the deposition thickness of the anodic electrodeposition catalyst increases. This is mainly due to the faster deposition rate, which shows that a higher potassium hydroxide concentration is beneficial to increase the deposition rate of the anodic electrodeposition catalyst. Therefore, in the process of preparing cobalt-based catalysts by electrochemical deposition, the concentration of the alkali solution KOH has an important influence on the performance of the prepared cobalt-based catalyst. Accordingly, the concentration of the KOH alkali solution can be 1 to 4M.
[0052] Therefore, the cobalt-based catalyst provided in the embodiment of the present invention is a mixture of nano-cobalt oxides and nano-cobalt hydroxides with different oxidation states, mainly using KCo(III)EDTA as a precursor, and is prepared by an in-situ electrochemical deposition method. The preparation method of the above-mentioned cobalt-based catalyst is simple and convenient, easy to control, and has good reproducibility. It does not require an additional binder to fix it, and can form a strong binding force with the electrode, and has good stability and is not easy to fall off; the above-mentioned cobalt-based catalyst is used as a catalyst for hydrogen production by electrolysis of water, has an obvious oxygen evolution reaction, can be used as an anode catalyst for hydrogen production by electrolysis of water, and is conducive to industrial application as a catalyst for hydrogen production by water electrolysis.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A cobalt-based catalyst, characterized in that It is mainly composed of nano cobalt oxide and nano cobalt hydroxide.
2. A method for preparing the cobalt-based catalyst according to claim 1, comprising electrolyzing KCo(III)EDTA by electrochemical deposition, wherein: KCo(III)EDTA is potassium ethylenediaminetetraacetylcobaltate, and its structural formula is 3. The preparation method according to claim 2, characterized in that: The method comprises first dissolving KCo(III)EDTA in an alkaline solution to form a cobalt-containing alkaline solution; and then performing electrochemical deposition to in-situ deposit a cobalt-based catalyst on the electrode surface.
4. The preparation method according to claim 3, characterized in that: The alkaline solution is a potassium hydroxide solution or a sodium hydroxide solution.
5. The preparation method according to claim 4, characterized in that: The concentration of the alkaline solution is 1-4M, and the dosage of KCo(III)EDTA is 0.5-3g / L.
6. The preparation method according to any one of claims 2 to 5, characterized in that: The electrochemical deposition step includes: using a three-electrode system, inserting a working electrode into the cobalt-containing alkaline solution for electrochemical deposition, and in-situ deposition on the working electrode to form the cobalt-based catalyst.
7. The preparation method according to claim 6, characterized in that: The working electrode is a carbon paper electrode, a glassy carbon electrode, a graphite electrode, an indium tin oxide electrode or a reduced graphene electrode.
8. The preparation method according to any one of claims 2 to 5, characterized in that: The preparation method of KCo(III)EDTA comprises: firstly keeping cobalt dichloride and EDTA at a constant temperature of 70 to 90°C for 15 to 30 minutes under stirring to form a pink suspension; then adding potassium acetate to the suspension under the constant temperature to transform the pink suspension into a magenta mixture; then adding excess hydrogen peroxide to the magenta mixture under the constant temperature, continuing to stir and react until the magenta mixture turns into a darker purple-red mixture; and hot filtering the purple-red mixture to obtain KCo(III)EDTA.
9. Use of the cobalt-based catalyst according to claim 1 in hydrogen production by electrolysis.
10. The use according to claim 9, characterized in that: The cobalt-based catalyst is used as an anode catalyst in the electrolysis of neutral water or seawater to produce hydrogen.
Citation Information
Cited By
Microwave-controlled graphene electrode cobalt-based complex molecular device and preparation method thereof
CN121815877A
Microwave manipulated graphene electrode cobalt-based complex molecular device and preparation method thereof
CN121815877B